PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP KINERJA PERUSAHAANPERBANKAN DI BURSA EFEK INDONESIA TAHUN 2013 - 2015 - Adiati, Yashita; Adiwibowo, Agustinus Santosa (Diponegoro Journal of Accounting, 2017)
This study aimed to obtain evidence about the effect of the audit committee charactersitic to bankin firms performance. The control variable used were Leverage.  Banking firms performance is measured by ROA. The characteristics of the audit committee examined herein are the composition of independent audit committees (INDE) as measured by the proportion of independent audit committees, financial expertise (FE) measured by appropriate weight, audit committee meetings (TM) are measured by the number of meetings conducted by banking companies, Members with a risk-monitoring committee (PR) and a remuneration nomination committee (NR) are also measured with the proportion of related members.The population in this study are all banking companies listed on the Indonesia Stock Exchange in 2013. The data selection method used in this research is purposive sampling method. Total samples used in this study as many as 78 companies. Data analysis was performed with the classical assumption and hypothesis testing regression method. The results of this study indicate that there is an insignificant relationship between the composition of the independent audit committee and the firms’s performance. This means that the audit committee's independence level has no effect on the firms’s performance. Similarly, audit committee meetings have no significant relationship with the performance of banking companies. In addition, this study indicates a significantly negative correlation between the linkage of the audit committee and the risk monitoring committee. The results of this study also indicate that the audit committee's financial expertise and the integrity of the audit committee with the remuneration nomination committee have an effect on the firms's performance.